MENINGKATKAN PERILAKU SOPAN PADA ANAK USIA 5-6 TAHUNMELALUI METODE BERCERITA - Ummi, Insyafiatul; Sitorus, Ahmad Syukri (Bunayya, 2026)
Politeness is an important aspect of moral development in early childhood. Initial observations at RA Azrina showed that most children aged 5–6 years were not yet accustomed to using polite expressions such as “please,” “thank you,” “sorry,” and “excuse me,” and did not consistently demonstrate behavior in accordance with politeness norms in their daily interactions. This study aimed to improve children's politeness through storytelling. The study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, conducted in two cycles with 20 Group B children at RA Azrina, Medan Marelan District. Data were collected using checklist observation sheets and documentation, and were analyzed descriptively using quantitative and qualitative approaches. The results showed that classical mastery increased from 0% in the pre-cycle stage to 25% in Cycle I and 90% in Cycle II. At the end of the study, 12 children (60%) achieved the Very Well Developed (VWD) category, 6 children (30%) reached the Developed as Expected (DE) category, and 2 children (10%) remained in the Beginning to Develop (BD) category. Thus, storytelling was effective in improving children's politeness through the delivery of moral messages in an engaging, contextual manner appropriate to the developmental characteristics of early childhood.